A CONSTITUIÇÃO FEDERAL E A ASCENSÃO DO SUPREMO TRIBUNAL FEDERAL: OS TRIBUNAIS NO SISTEMA JURÍDICO - Ribeiro, Diógenes V. Hassan (Revista da AJURIS - Qualis A2, 2020)
THE FEDERAL CONSTITUTION AND THE RISE OF THE SUPREME FEDERAL COURT: THE COURTS IN THE LEGAL SYSTEM ÁREA(S): direito constitucional. RESUMO: O artigo apresenta pesquisa sobre a ascensão do Supremo Tribunal Federal que iniciou com a Constituição Federal de 1988 e sobre a posição dos tribunais no sistema jurídico. O referencial teórico de partida é a Teoria dos Sistemas Sociais de Niklas Luhmann. Pretende-se apresentar, na história do constitucionalismo brasileiro, as funções ocupadas pelo Supremo Tribunal Federal. O problema central é se uma democracia emergente necessita de uma instância que lhe dê sustentação. Vincula-se esse problema às fragilidades do sistema de governo escolhido nas instituições democráticas emergentes do novo ordenamento jurídico. A história revela que as manifestações do poder soberano, em alguns momentos pontuais, dependeram das forças armadas. Todavia, o artigo defenderá que não é necessária, nem foi outorgada pela Constituição Federal, nenhuma função de prevalência do Supremo Tribunal Federal. ABSTRACT: The article presents research about the rise of the Supreme Federal Court that initiated with the Federal Constitution of 1988 and about the position of the courts in the legal system. The theoretical starting point is Niklas Luhmann’s Social Systems Theory. It is intended to present, in the history of Brazilian constitutionalism, the functions occupied by the Supreme Federal Court. The central problem is whether an emerging democracy needs an instance that supports it. This problem is linked to the fragilities of the system of government chosen in the emerging democratic institutions of the new legal system. History reveals that the manifestations of the sovereign power, at some specific moments, depended on the armed forces. However, the article will argue that is not necessary, nor was it granted by the Federal Constitution, a prevalence function of the Supreme Federal Court. PALAVRAS-CHAVE: tribunais; Constituição; democracia; teoria dos sistemas; Brasil. KEYWORDS: courts; Constitution; democracy; systems theory; Brazil. SUMÁRIO: Introdução; 1 A posição dos tribunais no sistema jurídico; 2 As crises políticas na história constitucional brasileira; 3 O presidencialismo e o parlamentarismo e suas crises; 4 O papel das Forças Armadas e do Supremo Tribunal Federal na solução das crises no modelo presidencialista; 5 A Constituição de 1988 e a ascensão do Supremo Tribunal na superação das crises; 6 A interpretação constitucional e o Supremo Tribunal Federal; Conclusões; Referências. SUMMARY: Introduction; 1 The position of the courts in the legal system; 2 Political crises in Brazilian constitutional history; 3 Presidentialism and parliamentarism and its crises; 4 The role of the Armed Forces and the Supremo Tribunal Federal in solving crises in the presidential model; 5 The 1988 Constitution and the rise of the Supremo Tribunal Federal in overcoming crises; 6 The constitutional interpretation and the Supremo Tribunal Federal; Conclusions; References.